Estudio de un Sistema de Comunicación para Interconectar el Sistema Informático de las Sucursales de Servientrega de la Ciudad de Babahoyo. - Escobar Acosta, Jennifer Carmen (2017)
Today with the rise of technological advances, communication systems are of great importance in almost all companies and organizations, since through it can be transmitted large amounts of data that are used in information systems, Communication systems allow information to be transmitted from a point called a source to another point called a destination. Data transmission is the exchange of data between two devices through some form of transmission medium, such as a cable. For data transmission to be possible, communication devices must be part of a communication system consisting of hardware (physical equipment) and software (programs). The effectiveness of the data communication system depends on four fundamental characteristics: delivery, accuracy, punctuality and variable delay. (Forouzan, 2007, p.4) Servientrega S.A. is a legally constituted company, with a national and international positioning, the same one that provides logistics services, fulfilling its fundamental management of, providing complementary support to the logistic needs and communication in an integral way with the clientele, transforming positive expectations into the service provided, the avant-garde impetus for the exhaustive refinement of the Labor Leaders and the sense of responsibility with Ecuadorian territory and its population. The company has 154 solution centers in the country. This company dedicated to the logistics service has proposed periods for delivery according to the need of customers, thus reaching different sectors of our country. The present case study allows to describe the problems that arise in the branches of Servientrega S.A. of the city of Babahoyo, in which it can be appreciated that there is discontent on the part of its clients, since they lose a great amount of time when approach to consult or request information about a specific requirement in a branch other than the one that was registered for the first time.